Integrating Diversity, Equity, and Inclusion into Systems Analysis and Design Education - Segooa, Mmatshuene Anna; Barber, Connie S (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
Diversity, Equity, and Inclusion (DEI) represent the involvement of different groups supported equally and fairly while their differences are acknowledged and recognized. Many organizations, including higher education institutions, have adopted the notion of DEI by introducing the phenomenon through their institutional strategies. However, there is limited evidence of the inclusion of DEI content in information systems (IS) education. The paper aimed to develop a framework to integrate DEI in Information Systems Analysis and Design education and projects. A survey to investigate how organizations actively include DEI content in the different stages of the System Development Lifecycle (SDLC) methodology was administered. Results identified that 23-40% of organizations represented address DEI at some stage of the SDLC. Practical implications for instructors include well-informed and prepared students as well as improved System Analysis & Design (SA & D) curriculum. The practical implications for information systems (IS) practitioners are resulting system designs that are culturally sensitive, end user perspective driven, and accessible for all users. Bridging IS education with industry practice through a framework for DEI in the system design space brings new insights into system design, better preparing students to face DEI content in their careers across all industries. Significantly raising awareness that problem solving and IS solutions should meet the needs of society with different backgrounds and cultures.